The Internet a global telecommunications solution?. - Mathy, L. (IEEE Network : the magazine of global information exchange)
The provision and support of new distributed multimedia services are of prime concern for telecommunications operators and suppliers. Clearly, the potential of the latest Internet protocols to contribute communications components is of considerable interest to them. In this article we first review some of the new types of application and their requirements, and identify the need to support applications that have strict QoS requirements, the so-called critical applications. We review two proposals for enhancing the Internet service architecture. In addition to the integrated services work of the IETF, we look at the proposals for differentiated services in the Internet. We then individually review protocol developments proposed to improve the Internet, and to support real-time and multimedia communications. These are IPv6 (the new version of the Internet Protocol), Resource reSerVation Protocol, and Multiprotocol Label Switching, respectively. In each case, we attempt to provide critical reviews in order to assess their suitability for this purpose. Finally, we indicate what the basis of the future infrastructure might be in order to support the full variety of application requirements